2016
DOI: 10.3389/fmicb.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Austrian Clinical Klebsiella and Enterobacter Isolates Linked to Patient-Related Data

Abstract: The aim of the study was to analyze the antimicrobial susceptibility of Austrian clinical Klebsiella sp. and Enterobacter sp. isolates linked to patient-related data over a time period from 1998 to 2014. The main findings of this study were (i) a marked difference of antibiotic susceptibility rates between different infection sites for both Klebsiella sp. and Enterobacter sp., (ii) significantly greater percentages of resistant isolates among both Klebsiella sp. and Enterobacter sp. in male patients compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…About 52.81% of the patients aged more than 63 years, 57.29% of the patients aged less than 47 years, and 60.10% of the patients aged between 48 and 63 years were male. Several previous studies found that the susceptibility rates of bacteria to antibiotics in male patients are different than those in female patients [ 23 , 24 , 25 , 26 ]. Further studies are needed to assess the difference in bacterial resistance between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…About 52.81% of the patients aged more than 63 years, 57.29% of the patients aged less than 47 years, and 60.10% of the patients aged between 48 and 63 years were male. Several previous studies found that the susceptibility rates of bacteria to antibiotics in male patients are different than those in female patients [ 23 , 24 , 25 , 26 ]. Further studies are needed to assess the difference in bacterial resistance between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Despite sex being a well-established risk factor for specific bacterial infections such as urinary tract infections, how prevalence of DRI varies between the sexes (and genders) is vastly underexplored in the literature [23]. This is despite many studies of infections caused by specific bacterial pathogens or syndromes finding a difference in resistance prevalence in infection between the sexes [24][25][26][27][28][29]. In 2018, the WHO called for countries to take the first step to better considering "gender and equity" in National Action Plans for AMR [30], which have historically lacked such considerations (e.g., in Southeast Asia [31]).…”
Section: Introductionmentioning
confidence: 99%
“…HIV) and bacterial infections such as urinary tract infections, how prevalence of drug-resistant infection (DRI) varies between the sexes (and genders) is vastly underexplored in the literature (20). This is despite many studies of single bacteria or syndromes finding a difference in resistance prevalence in infection between the sexes (21)(22)(23)(24)(25)(26). In 2018, the WHO called for countries to take the first step to better considering "gender and equity" in National Action Plans for AMR (27), which have historically lacked such considerations (e.g.…”
Section: Introductionmentioning
confidence: 99%